The importance of parental involvement in improving students' English subject performance in secondary school / Dayang Fatin Farhana Rashid - Rashid, Dayang Fatin Farhana (Faculty of Education, 2014)
The study was conducted to investigate the importance of parental involvement in improving students’ English subject performance in secondary school. It was intended to study the how far parental involvement is important in improving students’ English subject performance in secondary school. A total of 30 respondents consist of 8 English teachers from secondary school and 22 parents were chosen as participants. A descriptive method was used. For various reasons, results indicate parental involvement do help in improving students’ English subject performance in secondary school.